Effect of sintering aid MoO3 on the microstructure and ionic conductivity of ceria- and lanthanum gallate-based electrolytes. (2nd December 2018) - Wang, Jianqiu; Zhou, Defeng; Wang, Yuan; Meng, Jian; Zhang, Junbo
ABSTRACT: The effect of a small addition of MoO3 on the microstructure and ionic conductivity of Nd0.2 Ce0.8 O1.9 (NDC), La0.8 Sr0.2 Ga0.8 Mg0.2 O2.8 (LSGM) and Nd0.2 Ce0.8 O1.9 -La0.8 Sr0.2 Ga0.8 Mg0.2 O2.8 (NDC-LSGM) has been investigated. The microstructure and electrical properties of the samples were characterized by X-ray diffraction, field-emission scanning electron microscopy and electrochemical impedance spectroscopy. The results show that MoO3 doping can obviously increase the densification and grain sizes, and decrease the grain and grain boundary resistances of the NDC, LSGM and NDC-LSGM electrolytes. It expands the oxygen ion channels and reduces the total conductance activation energy of the system. The total conductivities of MoO3 -doped NDC and NDC-LSGM samples are 1.56 and 2.10 times higher than that of the undoped NDC system at 450°C. The total conductivity of LSGM-Mo is 1.46 times higher than that of LSGM at 450°C. These finding suggest that MoO3 is considered to be an effective sintering aid that optimizes the electrical properties of NDC, LSGM and NDC-LSGM electrolytes.